(untitled) (Revista Contexto & Educação, 2023)
The expansion and internalization of Professional and Technological Education (EPT) in the early decades of this century made the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN) expand from 2 to 22 its number of campuses distributed around all of the micro-regions of the State. The objective of this work is to discuss the new spatialization of the IFRN campuses and analyze the impacts brought by this policy of internalization of professional education in many levels, from initial training to superior and post-graduation. It is a qualitative research, with institutional documents analysis, such as: the Political-Pedagogical Project, the Institutional Development Plan and the Management Reports. It was also used statements of students covered by the expansion policy, in which the reports are found in the Portal in the site of the IFRN. The research showed the relevance of the expansion policy of the EPT for the democratization and social inclusion in the Rio Grande do Norte, by allowing the execution of personal projects that would hardly be achieved without the installation of an IFRN campus.